XALÍQTÍŃ JAS DÚZILISI HÁM KEKSELIKTIŃ DEMOGRAFIYALÍQ ANALIZI - Tulebaev, Seydulla Sağınıshbay ulı (SCIENCE and SOCIETY, 2026)
The article primarily examines the aging process of the population, the demographic characteristics of aging, its formation factors, and the impact of societal development from a scientific perspective. Based on demographic indicators of the world and Uzbekistan, trends in the increase in the share of the elderly are reflected in statistical data. Statistical data related to population aging are also considered.